Low-Dose Perfusion Computed Tomography for Breast Cancer to Quantify Tumor Vascularity: Correlation With Prognostic Biomarkers. Issue 5 (May 2019) - Park, Eun Kyung; Seo, Bo Kyoung; Kwon, Myoungae; Cho, Kyu Ran; Woo, Ok Hee; Song, Sung Eun; Cha, Jaehyung; Lee, Hye Yoon
Abstract : Objectives: The aim of this study was to investigate the feasibility of using low-dose perfusion computed tomography (CT) in breast cancers for quantification of tumor vascularity and to correlate perfusion indexes with prognostic biomarkers. Materials and Methods: This preliminary study was approved by our institutional review board. Signed informed consent was obtained from all 70 enrolled patients with invasive breast cancers. Low-dose perfusion CT was performed with the patient in the prone position using a spectral CT device set at 80 kVp and 30 mAs (1.30–1.40 mSv). Images were analyzed using commercial software applying the maximum slope algorithm. On CT perfusion maps, perfusion (mL/min per 100 mL), blood volume (mL/100 g), time-to-peak enhancement (second), and peak enhancement intensity (HU) were measured in the tumor, normal breast glandular tissues, and fat. Tumor grade, estrogen receptor (ER), human epidermal growth factor receptor 2 (HER2), and Ki67 level were evaluated using histopathology. Statistically, CT perfusion indexes of the tumor and normal glandular tissues or fat were compared using the Wilcoxon signed-rank test, and CT indexes were correlated with histological characteristics using the Mann-Whitney U or Kruskal-Wallis tests. We also correlated CT indexes with magnetic resonance imaging enhancement characteristics. Results: In breast cancers, perfusion, blood volume, and peak enhancement intensity values were significantly higher, and time to peak was shorter than in normal glandular tissues and fat ( P < 0.001). Perfusion increased significantly in high-grade, ER–, or HER2+ cancers ( P < 0.05). Time to peak decreased in ER–, HER2+, and high-grade cancers or in those with high Ki67 levels ( P < 0.05). Peak enhancement intensity significantly increased in high-grade cancers ( P < 0.05). HER2 overexpressing cancers showed significantly higher perfusion and shorter time to peak than luminal-type cancers ( P < 0.05). Perfusion increased and time to peak decreased significantly in cancers with washout enhancement patterns on magnetic resonance imaging. Conclusions: Low-dose perfusion CT in the prone position is feasible to quantify tumor vascularity in breast cancers, and CT perfusion indexes are significantly correlated with prognostic biomarkers and molecular subtypes of breast cancer.